Implementasi Konsep CARE (Collaborative, Active, Respect, Educative) dalam Perancangan Interior Student Center di Universitas Kristen Petra - Kosaladarma, Gloria Puspitadewi; Thamrin, Diana; Rakhmawati, Anik (Intra, 2018)
Petra Christian University has various lecture and student activities. Lecture activities at Petra Christian University have adequate facilities, but other activities, such Student Organization, need better facilities to optimize the internal coordination process. The main objective of this design is to provide a place that accommodate student's social and recreation needs also to improve the coordination among Student Organizations. The design method for the Student Center design consists of Understand, Observe, Point of View, Ideate, Prototype, and Test. Through Understand, Observe and Point of View stages, basic problems are found and design concept in Ideate stage is formed. The final design results a Student Center with CARE (Collaborative, Active, Respect, Educative) concept. The interior and furniture elements are designed to stimulate students to socialize, coordinate and play together. In addition, the design is expected to form a good behavior for students at Petra Christian University.